2008
DOI: 10.1016/j.jpurol.2007.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Evolving management of adolescent varicocele

Abstract: Objective: To review the evolution in indications for treatment and treatment modalities for adolescent varicocele at our centre, and evaluate the impact of varicocelectomy on final outcome. Patients and methods: Between 1995 and 2006, we treated 242 left varicoceles. Preoperative assessment included clinical evaluation, measurement of testicular volumes, and colourDoppler ultrasound (CDUS). A subinguinal varicocelectomy was performed in 124 patients (group A), and a laparoscopic non-artery-sparing Palomo proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Diamond et al reported abnormal sperm count in 11% and 59% of patients with testicular volume discrepancy of 10%-20% and >20%, respectively (5). Surgical repair of varicocele improves semen parameters in infertile men (12) and the prevalence of testicular catch-up growth has been reported to be as high as 80% after varicocelectomy (13)(14)(15). Patients with varicocele and no evidence of testicular hypotrophy may be eligible for a conservative nonsurgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Diamond et al reported abnormal sperm count in 11% and 59% of patients with testicular volume discrepancy of 10%-20% and >20%, respectively (5). Surgical repair of varicocele improves semen parameters in infertile men (12) and the prevalence of testicular catch-up growth has been reported to be as high as 80% after varicocelectomy (13)(14)(15). Patients with varicocele and no evidence of testicular hypotrophy may be eligible for a conservative nonsurgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…This result came in accordance to Castagnetti et al who compared 96 cases of subinguinal varicocelectomy plus pre-emptive hydrocelectomy with 46 patients who underwent subinguinal varicocelectomy alone. [19][20][21] The rate of postoperative hydrocele was statistically lower in those who received a pre-emptive hydrocelectomy (4.2% versus 13%; P = 0.04). Pre-emptive surgery can consist of vaginalis excision only or excision and eversion.…”
Section: Discussionmentioning
confidence: 97%
“…9 Subsequently, a modified laparoscopic technique was developed that was also able to address reflux in the def erential vein shown by CDUS (Figure 9). [6][7][8] Using this approach, surgeons have managed to progressively lower persistence rates.…”
Section: Surgical Treatment Optionsmentioning
confidence: 99%
“…It enables assessment of the functional anatomy subtending the varicocele [6][7][8] and provides a comprehensive evaluation of the three major venous networks draining the pampiniform plexus-the ISV, the cremasteric veins, and the defer ential veins-distinguishing refluxing collateral and differentiating refluxing veins from veins dilated due to overflow. 9 In a recent study of 148 adolescent and pedi atric patients, CDUS identified reflux in the ISV alone in 126 patients (85.1%), reflux in both the ISV and the deferential vein in 21 patients (14.1%), and an isolated deferential reflux in one patient (0.6%).…”
Section: Introductionmentioning
confidence: 99%